Intracellularly stored polysulfur maintains homeostasis of pH and provides bioenergy for phosphorus metabolism in the sulfur-associated enhanced biological phosphorus removal (SEBPR) process. (November 2019) - Zhao, Qing; Yu, Mei; Zhang, Xin; Lu, Hui; Biswal, Basanta Kumar; Chen, Guang-Hao; Wu, Di
Abstract: Sulfur-associated enhanced biological phosphorus removal has recently been developed for the removal of biological nutrients. In this new bioprocess, the polymeric sulfur compound (poly-S) is crucial to connecting sulfur conversions and polyphosphate accumulation; however, its mechanisms are still elusive. This study investigated the role of poly-S in maintaining the system stability by operating a lab-scale reactor for 720 d and conducting batch experiments with various initial pH values. The main findings were as follows: i) intracellular poly-S increased from 30 to 95 mg S (g VSS) −1, whereas polyhydroxyalkanoates increased from 8 to 22 mg C (g VSS) −1 ; ii) glycogen increased from 7.5 to 12.5 mg C (g VSS) −1 during the first 520 d before decreasing; and 3) P removal could be maintained at 8–12.5 mg P (L) −1 . The decrease in glycogen was likely because the accumulation of enough poly-S could replace glycogen to provide reducing power and buffer the inner pH. The results of batch tests confirmed that poly-S could adjust the intracellular protons under anaerobic conditions (pH always returned to neutral or neutral levels at the end of anaerobic phase) and provide cellular bioenergy (adenosine triphosphate, for P uptake, thereby maintaining net P removal). The predominant microbial communities were facultative denitrifying Thauera (11%), sulfide-oxidizing Thiobacillus (8%), and sulfate-reducing Desulfobacter (9%). However, the conventional polyphosphate-accumulating organisms were detected at very low abundance (e.g. Tetrasphaera at only 0.02%). Overall, poly-S could regulate intracellular protons and energy balance and reduce glycogen accumulation, keeping good biological P removal performance. Highlights: This study assessed the impact of intracellularly stored poly-S on pH homeostasis. Intracellular poly-S and PHAs during the 700-day reactor operation. Glycogen increased to 12 mg C (g VSS) −1 during the first 520 days before decreasing. Biological P removal was independent of poly-S increase and glycogen decrease. Poly-S adjusts the pH around 7 and supply energy for P removal.